2016
DOI: 10.1186/s12933-016-0406-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between omentin-1 expression in human epicardial adipose tissue and coronary atherosclerosis

Abstract: BackgroundOmentin-1, a novel adipocytokine mainly expressed in visceral adipose tissue, has been found to inhibit the inflammatory response and improve insulin resistance as well as other obesity-related disorders. This study investigated the association between omentin-1 expression in human epicardial adipose tissue (EAT) and coronary atherosclerosis.MethodsSerum samples, and paired biopsies from EAT and subcutaneous adipose tissue (SAT), were obtained from patients with and without coronary artery disease (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 33 publications
5
86
1
5
Order By: Relevance
“…In general, omentin is thought to have a protective function in CVD [44,45]. Omentin is also evident in human epicardial adipose tissue, with a reduced expression being related to coronary artery stenosis [46]. These observations contradict the results of a recent 3.5-year prospective observational study which showed that high plasma omentin concentrations might serve as a biomarker for an enhanced risk of cardiovascular mortality in patients with established or suspected stable coronary artery disease [47].…”
Section: Low-grade Inflammation Of Adipose Tissue: a Major Link To Vacontrasting
confidence: 56%
“…In general, omentin is thought to have a protective function in CVD [44,45]. Omentin is also evident in human epicardial adipose tissue, with a reduced expression being related to coronary artery stenosis [46]. These observations contradict the results of a recent 3.5-year prospective observational study which showed that high plasma omentin concentrations might serve as a biomarker for an enhanced risk of cardiovascular mortality in patients with established or suspected stable coronary artery disease [47].…”
Section: Low-grade Inflammation Of Adipose Tissue: a Major Link To Vacontrasting
confidence: 56%
“…With respect to CVD, circulating omentin was decreased in patients with coronary artery disease and appeared to have a protective role in patients with ischaemic stroke . In line, administration of omentin in mice reduced tissue damage after ischaemia/reperfusion and delayed the development of aortic atherosclerotic lesions with reduced vascular inflammation …”
Section: Introductionmentioning
confidence: 72%
“…[2][3][4][5] These findings were supported by in vitro studies showing that omentin increased Akt phosphorylation and insulin-stimulated glucose uptake in human adipocytes. 1 With respect to CVD, circulating omentin was decreased in patients with coronary artery disease 6,7 and appeared to have a protective role in patients with ischaemic stroke. 8,9 In line, administration of omentin in mice reduced tissue damage after ischaemia/reperfusion 10 and delayed the development of aortic atherosclerotic lesions with reduced vascular inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…1). Particularly, omentin-1, a novel EAT-derived circulating anti-inflammatory and insulin sensitizer adipokine, was reduced in patients with CAD [47]. …”
Section: Eat Dysfunction and Cardiovascular Riskmentioning
confidence: 99%